Determining Obstetric Patient Safety Indicators: The Differences in Neonatal Outcome Measures Between Different-sized Delivery Units. Issue 1 (March 2015) - Pyykönen, A.; Gissler, M.; Jakobsson, M.; Petäjä, J.; Tapper, A.M.
Abstract : ( BJOG . 2014;121(4):430–437)